2016
DOI: 10.1002/mrm.26292
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of bound and pore water T1relaxation times in cortical bone using three-dimensional ultrashort echo time cones sequences

Abstract: Purpose We present three dimensional ultrashort echo time Cones (3D UTE Cones) techniques for quantification of total water T1s (T1TW), bound water T1s (T1BW) and pore water T1s (T1PW) in vitro and in vivo using a 3T scanner. Methods T1TW, T1BW and T1PW were measured with 3D Cones and adiabatic inversion recovery Cones (IR-Cones) sequences. 2D non-selective UTE techniques, including saturation recovery, variable TRs, and IR preparation approaches were compared with 3D-Cones techniques on bovine cortical bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 43 publications
4
57
1
Order By: Relevance
“…Although direct imaging of cortical bone has previously been presented at different locations such as the midshaft of the tibia [28,[32][33][34], direct imaging of the hip is considered of higher clinical significance since fractures at this location are more devastating [3]. In addition, imaging at this location is considered more technically challenging.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although direct imaging of cortical bone has previously been presented at different locations such as the midshaft of the tibia [28,[32][33][34], direct imaging of the hip is considered of higher clinical significance since fractures at this location are more devastating [3]. In addition, imaging at this location is considered more technically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies employing the UTE sequence have shown that both bound water (short T 2 ⁎ component) and pore water (long T 2 ⁎ component) in cortical bone can be quantified using a bi-component T 2 ⁎ analysis technique [18,[25][26][27][28]. Moreover, T 2 ⁎ decay time for bound water in cortical bone can be measured with the IR-UTE technique by suppressing the signal from the pore water and then using a single component analysis of the remaining signal [27,29,38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations